Impact of training and competition load on neuromuscular recovery, hormonal response and match performance in association football - Rowell, A. E. (Victoria University Melbourne, 2018)
In team sports, the competition season requires a balance between training and recovery. To assist in this process, both internal and external load are quantified. External load can be measured using Global Positioning Systems (GPS) and sensors such as accelerometers. Internal load is commonly identified through session rating of perceived exertion (sRPE), biochemical response in addition to changes in performance tests. However, little is known about the interaction between training load, the response to this load, and performance. Study 1 determined the response of countermovement jump (CMJ) performance and salivary testosterone and cortisol to low, medium and high accelerometer derived PlayerLoad™ following football match play. Flight time:contraction time (FT:CT) was the most sensitive CMJ metric, with a dose-response reduction for 42h post-match. There were post-match increases in testosterone and cortisol irrespective of PlayerLoad™ level, and substantial variability which limits the usefulness of hormonal markers. Study 2 assessed the impact of training and competition load throughout a professional football season on FT:CT, testosterone, cortisol and testosterone:cortisol and match performance. The largest effects of internal load on performance occurred in the 3- to 14-day pre-match window. An association between increased load and lower rating of performance was identified in defenders, whilst strikers and wide midfielder`s performance rating was higher with higher load. Change in load did not substantially impact FT:CT or the hormonal response, and there was limited impact of these measures on performance. Study 3 examined the use of a commonly used football training drill; small sided game (SSG), for measurement of neuromuscular fatigue (NMF). Whilst high weekly load increased accelerometer derived metrics during the SSG, these modifications did not appear to be fatigue related. Lower FT:CT compared to baseline, was related to reductions in accelerometer derived variables during the SSG. The reductions in FT:CT and accelerometer variables in the SSG were followed by the same modifications to match activity profile. Therefore, a standardised SSG game may be a useful tool for the assessment of NMF. This thesis provides insights into the links between training and competition load, the response to that load, and the impact on performance in elite male football players. The results offer practitioners useful approaches to monitor athletes and maximise their performance. Finally, this thesis demonstrates the utility of an SSG for the assessment of NMF.